2021
DOI: 10.1002/adfm.202104645
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Delivered Supramolecular Nanomedicine with Transformable Shape for Ferrocene‐Amplified Photodynamic Therapy of Breast Cancer and Bone Metastases

Abstract: Although nanomedicines can passively target tumor through the enhanced permeability and retention (EPR) effect, their distribution and retention are limited by complex tumor microenvironment. Herein, a self-delivery supramolecular nanoplatform with shape-transforming capacity (Ce6-CD/ Fc-pep-PEG) is constructed by the host-guest interaction between chlorin e6-conjugated β-cyclodextrin (Ce6-CD) and ferrocene-modified FFVLG 3 C-PEG conjugates (Fc-pep-PEG). Following passive accumulation mediated by the EPR effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 55 publications
1
73
0
Order By: Relevance
“…86 Furthermore, Fenton or Fenton-like reactions are vital in chemodynamic therapy and photodynamic therapy, facilitating synergetic cancer therapy. 87,88…”
Section: Endogenous Stimuli-responsive Supramolecular Assembliesmentioning
confidence: 99%
See 2 more Smart Citations
“…86 Furthermore, Fenton or Fenton-like reactions are vital in chemodynamic therapy and photodynamic therapy, facilitating synergetic cancer therapy. 87,88…”
Section: Endogenous Stimuli-responsive Supramolecular Assembliesmentioning
confidence: 99%
“…Yi et al optimized this kind of ROS self-enhanced system by endowing the system with shape-transforming capacity. 88 At the tumor site, the guest moiety, Fc-modified FFVLG 3 C-PEG, dissociated from the host moiety, chlorin e6-conjugated β-CD, thus formed nanofibers in a physiological environment. Meanwhile, the smaller micelles formed by host moieties penetrated to the deeper site of the tumor.…”
Section: Endogenous Stimuli-responsive Supramolecular Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cell-based experiments demonstrated that the constructed self-assembly has effective cytotoxicity and active targeting capability. 55 In Gao's group, many self-assembled nanoplatforms were constructed for multimodal combined treatment of breast cancer. 56,57 For instance, a macrophage membrane covered shape changeable nanomedicine(I-P@NPs@M) was reported for chemotherapy, PDT and immunotherapy of breast cancer.…”
Section: Drug-drug Self-assemblymentioning
confidence: 99%
“…In addition, cell-based experiments demonstrated that the constructed self-assembly has effective cytotoxicity and active targeting capability. 55…”
Section: Carrier-free Self-assembled Nanodrugsmentioning
confidence: 99%